Level of Student Knowledge About Pulmonary Tuberculosis at Medistra Health Institute Lubuk Pakam - Gurusinga, Rahmad (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pulmonary tuberculosis (TB) remains a significant health problem in Indonesia due to its contagious nature. Having an adequate understanding of TB is very important, especially for students in health education institutions, considering their potential role as pioneers in efforts to prevent and control this disease. This study was conducted to examine the level of knowledge of students regarding pulmonary tuberculosis at the Medistra Health Institute, Lubuk Pakam. This study used a quantitative descriptive method with a cross-sectional approach. A total of 100 students were used as research samples selected through purposive sampling techniques. Data collection was carried out using a closed questionnaire that had undergone validity and reliability tests. The data were then analyzed descriptively with a frequency distribution approach. The results showed that the majority of students, namely 65%, had a good level of knowledge about pulmonary TB. Meanwhile, 25% of respondents had knowledge in the sufficient category, and 10% were classified as lacking. The knowledge that was most widely mastered included the symptoms and transmission of TB, while aspects of prevention and treatment still need to be improved. The conclusion of this study shows that students at the Medistra Health Institute, Lubuk Pakam, generally have good knowledge regarding pulmonary TB. However, increased education on certain aspects is still needed. The results of this study are expected to be a reference for institutions in designing more comprehensive health promotion and education programs related to tuberculosis.